1992
DOI: 10.1128/jb.174.5.1544-1553.1992
|View full text |Cite
|
Sign up to set email alerts
|

Locating essential Escherichia coli genes by using mini-Tn10 transposons: the pdxJ operon

Abstract: The mini-TnlO transposon (A16A17TnJO) confers tetracycline resistance. When inserted between a gene and its promoter, it blocks transcription and prevents expression of that gene. Tetracycline in the medium induces divergent transcription of the tetA and tetR genes within the transposon, and this transcription extends beyond the transposon in both directions into the bacterial genes. If the mini-TnlO inserts between an essential bacterial gene and its promoter, th,e insertion mutation can cause conditional gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
88
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 27 publications
4
88
0
Order By: Relevance
“…The results of this study show that the AEra protein exhibited a reduced GTP-hydrolysis activity and an increased GTP-binding activity, and failed to bind to the E. coli cytoplasmic membrane. The truncated era (Aera) gene was unable to complement an E. coli mutant defective in Era production (Takiff et al, 1989(Takiff et al, , 1992. Together, these results suggest that the Cterminus of the Era protein is essential for the in viuo function of the protein.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…The results of this study show that the AEra protein exhibited a reduced GTP-hydrolysis activity and an increased GTP-binding activity, and failed to bind to the E. coli cytoplasmic membrane. The truncated era (Aera) gene was unable to complement an E. coli mutant defective in Era production (Takiff et al, 1989(Takiff et al, , 1992. Together, these results suggest that the Cterminus of the Era protein is essential for the in viuo function of the protein.…”
Section: Introductionmentioning
confidence: 68%
“…HT120 contains a mini-Tnl0 insertion upstream of the rnc gene which forms part of an operon with its downstream gene, era (Takiff et af., 1989(Takiff et af., , 1992. The mini-Tn 2 0 carries two divergent Tet-inducible promoters (Takiff et al, 1989(Takiff et al, , 1992. In the absence of Tet, HT120 could not grow on LB plates because the mini-Tnl0 insertion is downstream polar to era, which in turn blocks the transcription of the era gene.…”
Section: Fig 2 Lmmunodetection Of Cellular Amounts Of the Era Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Takiff et al (10) first identified the E. coli open reading frame containing the gene that encodes AcpS. At the time, this gene was of unknown function and was named dpj.…”
mentioning
confidence: 99%